Antimycobacterial and healing effects of Pranlukast against MTB infection and pathogenesis in a preclinical mouse model of tuberculosis - Rajmani, Raju S.; Surolia, Avadhesha (Frontiers in Immunology, 2024)
It is essential to understand the interactions and relationships between Mycobacterium tuberculosis (Mtb) and macrophages during the infection in order to design host-directed, immunomodulation-dependent therapeutics to control Mtb. We had reported previously that ornithine acetyltransferase (MtArgJ), a crucial enzyme of the arginine biosynthesis pathway of Mtb, is allosterically inhibited by pranlukast (PRK), which significantly reduces bacterial growth. The present investigation is centered on the immunomodulation in the host by PRK particularly the activation of the host's immune response to counteract bacterial survival and pathogenicity. Here, we show that PRK decreased the bacterial burden in the lungs by upregulating the population of pro-inflammatory interstitial macrophages (IMs) and reducing the population of Mtb susceptible alveolar macrophages (AMs), dendritic cells (DCs), and monocytes (MO). Additionally, we deduce that PRK causes the host macrophages to change their metabolic pathway from fatty acid metabolism to glycolytic metabolism around the log phage of bacterial multiplication. Further, we report that PRK reduced tissue injury by downregulating the Ly6C-positive population of monocytes. Interestingly, PRK treatment improved tissue repair and inflammation resolution by increasing the populations of arginase 1 (Arg-1) and Ym1+Ym2 (chitinase 3-like 3) positive macrophages. In summary, our study found that PRK is useful not only for reducing the tubercular burden but also for promoting the healing of the diseased tissue.